Morpho-anatomical and morphometric studies of the floral structures of the distylous Oldenlandia salzmannii (Rubiaceae) - Mariela Nuñez Florentin; Andrea Cabaña Fader; Ana Maria Gonzalez (Acta Botânica Brasílica)
ABSTRACT The genus Oldenlandia (Rubiaceae) has a conflicting generic delimitation, with representatives that show different floral syndromes. Oldenlandia salzmannii is a marshy herb that is widespread in South America. It is heterostylous, specifically distylous, and self-compatible. Recent molecular phylogenetic studies found that this species forms a clade that is isolated from the remaining described taxa of Oldenlandia. Information about the floral anatomy and reproductive biology of genera in the Spermacoceae tribe, particularly Oldenlandia, is insufficient, especially among the neotropical species. Accordingly, the present study aimed at contributing information on the reproductive biology of Oldenlandia salzmannii by analyzing its floral morpho-anatomy, morphometrics and phenology of both floral morphs. These analyses were conducted with natural, cultivated and fixed material using optical and scanning electron microscopes. Morphologically, the species is typically heterostylous with two floral morphs, long-styled and short-styled, the main difference being the indument of the corolla. The short-styled flowers have larger anthers and pollen grains. Morphometrics show a high degree of herkogamic reciprocity. The mature ovules have a hemitropous position, which is the first record of this position for the Spermacoceae tribe. This study represents the first comprehensive morphological study of Oldenlandia salzmannii.